Mental health of Hong Kong university students: a 5.5-year trend study across the COVID-19 pandemic - Jia-Yan Pan; Nana Wang; Michelle Hei Yan Shum (International Journal of Adolescence and Youth)
This study investigated the trend of the mental health status of Hong Kong university students before and during the 2019 social movement and COVID-19 pandemic. A total of 960 Hong Kong university students completed an online questionnaire in 11 cohorts from 2016 to 2021 in a trend study. In the sample, 68.5% showed various levels of depressive symptoms, and 49.4% were identified to be at-risk for developing mental health problems. The percentage of students with various levels of depressive symptoms and at-risk cases increased from 41.5% and 24.4% in 2016 to 80.0% and 60.0% in 2021, respectively. Overall deterioration of mental health was observed for Hong Kong university students from 2016 to 2021. Furthermore, results showed that positive thoughts, sense-making coping, and resilience functioned as significant protective factors, while negative thoughts and suicidal ideation acted as significant risk factors of various mental health outcomes of Hong Kong university students.